2020
DOI: 10.1002/jbm.b.34786
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of 58S bioactive glass based scaffold with Kaempferol‐containing Zein coating for bone tissue engineering

Abstract: The aim of this study was to prepare a porous scaffold out of 58S bioactive glass as the bare and coated with Zein to improve mechanical properties and acting as a carrier for Kaempferol controlled delivery. Porosity and morphology, mechanical properties, drug release behavior, bioactivity, cell attachment, and biodegradation of the scaffolds were evaluated accordingly. Obtained results indicated that the scaffolds coated by (7wt/v %) Zein solution, showed the highest mechanical strength (3.06 ± 0.4 MPa) and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…A recent study showed that 58S BG coated with Zein achieve could sustained release of kaempferol in 9 days. The concentration with 20 μM sample was not toxic for BMSC cells according to the MTT results (Ranjbar et al, 2021). In addition, kaempferolloaded TiO 2 showed sustained release within 168 h, and promoted the rat BMSCs proliferation and osteogenic differentiation with increasing mRNA expressions of Runx2, OCN, ON, OPN, and ALP in vitro culture, and promoted new bone formation surrounding the TiO 2 implants at 2 and 4 weeks after implantation iv vivo (Tsuchiya et al, 2018).…”
Section: Kaempferolmentioning
confidence: 79%
“…A recent study showed that 58S BG coated with Zein achieve could sustained release of kaempferol in 9 days. The concentration with 20 μM sample was not toxic for BMSC cells according to the MTT results (Ranjbar et al, 2021). In addition, kaempferolloaded TiO 2 showed sustained release within 168 h, and promoted the rat BMSCs proliferation and osteogenic differentiation with increasing mRNA expressions of Runx2, OCN, ON, OPN, and ALP in vitro culture, and promoted new bone formation surrounding the TiO 2 implants at 2 and 4 weeks after implantation iv vivo (Tsuchiya et al, 2018).…”
Section: Kaempferolmentioning
confidence: 79%
“…In addition, the findings indicate that the developed scaffolds could facilitate an optimal kaempferol discharge and a favorable atmosphere for cell adhesion ( Figure A). [ 143 ] Therefore, scaffold coated with zein could be considered a feasible alternative for bone regeneration.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Reproduced with permission. [ 143 ] Copyright 2021, John Wiley and Sons. B) SEM illustrations of C2C12 cells following 1 week of culture on a) zein and b) zein/nHA scaffolds, respectively.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…This form of kaempferol administration is a prospective solution for drug delivery systems [ 174 ]. Zein-kaempferol coatings improve the mechanical and bioactive properties of scaffolds, thus their tissue engineering application is justified [ 175 ]. The biopolymer-based membrane doped with kaempferol could be potentially applied as an infected wound dressing [ 176 ].…”
Section: Classification Of Flavonoidsmentioning
confidence: 99%